Drivers of Megabenthic Community Structure in One of the World’s Deepest Silled-Fjords, Sognefjord (Western Norway) - Meyer, Heidi K.; Roberts, Emyr M.; Mienis, Furu; Rapp, Hans T. (Frontiers in Marine Science, 2020)
The Sognefjord is the longest (205 km) and deepest (1308 m) fjord in Norway, and the second-longest in the world. Coast-fjord exchange in Sognefjord is limited by a seaward sill at 170 m water depth, which causes a clear stratification between water masses as the dense oxygen-poor basin water mixes slowly with the well-oxygenated water directly above from the coastal ocean. Due to the homogeneity and limited variability in the deep-water, the deep slopes of Sognefjord represent the ideal setting to study how abiotic factors influence the deep-water benthic community structure. During the summer of 2017, two remotely operated vehicle (ROV) video transects were performed to compare the megabenthic community behind the sill (water depth: 1230 to 55 m; transect length: 1.39 km; distance from sill: ~17 km) and within the central fjord (water depth: 1155 – 85 m; transect length: 2.43 km; distance from sill: ~79 km). Accompanying conductivity-temperature-depth (CTD) deployments were made to measure the in situ abiotic factors and nutrient concentrations at each transect location, while the substrate characteristics (percent cover of soft and hard exposed substrate) were documented from the video footage. Here, Sognefjord’s megabenthic community composition, distribution, and species richness were analyzed in relation to abiotic factors (e.g. depth, salinity, dissolved oxygen, chlorophyll a concentration, and percent cover of hard and soft substrata) within the fjord. Basin communities were homogeneous and characterized by sponges, echinoderms, and crustaceans, whereas the shallower regions were dominated by mobile scavengers. Contrary to other fjord-based studies, species richness and diversity were stable in the fjord basin and decreased with proximity to the sill, decreasing water depth, and at the boundary between intermediate and basin water. The findings demonstrate that highly stratified fjords support stable communities in their basins; however, further research is needed to investigate the influence water mass dynamics have on silled-fjord megafauna communities.